Transcriptome and metabolome analysis reveals the effect of flavonoids on flower color variation in Dendrobium nobile Lindl. - Qiu, Yujie; Cai, Chengcheng; Mo, Xu; Zhao, Xinyi; Wu, Lijuan; Liu, Fan; Li, Rui; Liu, Chen; Chen, Ji; Tian, Mengliang (Frontiers in Plant Science, 2023)
Dendrobium nobile L. is a rare orchid plant with high medicinal and ornamental value, and extremely few genetic species resources are remaining in nature. In the normal purple flower population, a type of population material with a white flower variation phenotype has been discovered, and through pigment component determination, flavonoids were preliminarily found to be the main reason for the variation. Hence, this study mainly explored the different genes and metabolites at different flowering stages and analysed the flower color variation mechanism through transcriptome-and flavonoid-targeted metabolomics. The results identified 1382, 2421 and 989 differentially expressed genes (DEGs) in the white flower (WF) variety compared with the purple flower (PF) variety at S1 (bud stage), S2 (chromogenic stage) and S3 (flowering stage), respectively. Among these, 27 genes enriched in the ko00941, ko00942, ko00943 and ko00944 pathways were screened as potential functional genes affecting flavonoid synthesis and flower color. Further analysis revealed that 15 genes are potential functional genes that lead to flavonoid changes and flower color variations. The metabolomics results at S3 found 129 differentially accumulated metabolites (DAMs), which included 8 anthocyanin metabolites, all of which (with the exception of delphinidin-3-o-(2'''-omalonyl) sophoroside-5-o-glucoside) were found at lower amounts in the WF variety compared with the PF variety, indicating that a decrease in the anthocyanin content was the main reason for the inability to form purple flowers. Therefore, the changes in 19 flavone and 62 flavonol metabolites were considered the main reasons for the formation of white flowers. In this study, valuable materials responsible for flower color variation in D. nobile were identified and further analyzed the main pathways and potential genes affecting changes in flavonoids and the flower color. This study provides a material basis and theoretical support for the hybridization and molecular-assisted breeding of D. nobile.The abbreviation description has been added.批注 [A2]: Specific description of the identification of the "S1, S2, S3" period has been added.The abbreviation description has been added.